Economic Vulnerability, Climate Change, and its Influence on School Enrolment: A Study of Dambatta Rural Community - Abduljalal Salisu; Aniek Hindrayani; Feri Setyowibowo; Adamu Zakiyu Ubale (UNIVERSITAS NEGERI SURABAYA, 2026)
Objective: The present study focused on exploring the influence of parents’ economic vulnerability in the agricultural sector on students’ enrollment in the Dambatta Local Government Area of Kano State, a rural community in Nigeria. Method: The quantitative and qualitative methods (mixed mode) were employed throughout this study. Two separate questionnaires were administered to 108 teachers and 28 parents who were randomly selected for interview. Results: indicates a moderate negative relationship between vulnerability in economic and students’ school enrolment in the rural community, with r = -0.686, p = 0.000, P < 0.01. That means an increase in vulnerability in agricultural jobs leads to a decrease in students’ enrolment. However, it was discovered that most parents in the rural community hold negative views regarding their children’s education during economic vulnerability. Novelty: The study signified that economic vulnerability caused by climate change, like negative precipitation and agricultural productivity, directly influences school conditions and educational decisions in rural communities.